2014
DOI: 10.1590/s2317-643120140003000011
|View full text |Cite
|
Sign up to set email alerts
|

Habilidade auditiva em criança desnutrida

Abstract: Purpose: To characterize and compare the performance of malnourished children and normal children in auditory processing. Methods: The sample comprised 30 children from five to ten years old, both genders, being 15 malnourished children (G1) and 15 children with adequate nutritional status, as a control group (G2). The groups were paired according to gender, age and grade level. Both groups underwent peripheral and central auditory assessment, noting that malnourished children had higher changes in the skill o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
5
Order By: Relevance
“…The effect of malnutrition on hearing and language, as observed in this study, has also been observed in other studies. [20][21][22] Previous studies [20][21][22] have shown that malnutrition causes delay in maturation of the auditory pathway and also affects both central and peripheral hearing. Nutritional deficiencies, even in acute form, impair the normal functioning of the middle ear, with negative consequences for the entire auditory system.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of malnutrition on hearing and language, as observed in this study, has also been observed in other studies. [20][21][22] Previous studies [20][21][22] have shown that malnutrition causes delay in maturation of the auditory pathway and also affects both central and peripheral hearing. Nutritional deficiencies, even in acute form, impair the normal functioning of the middle ear, with negative consequences for the entire auditory system.…”
Section: Resultsmentioning
confidence: 99%
“…Após a leitura completa, um trabalho foi excluído por tratar-se de uma tese de doutorado, cujos resultados já estavam descritos em outro artigo aceito para esta revisão. Os três trabalhos aceitos para esta revisão descreveram estudos realizados no Brasil, dois escritos em Português 14,18 e um em Inglês. 16 As Tabela 2, Tabela 3 e Tabela 4 apresentam as características e os resultados dos trabalhos sobre a alteração de PAC em sujeitos com diagnóstico e/ou histórico de desnutrição.…”
Section: Resultsunclassified
“…9,10 Essa alimentação, quando insuficiente em proteínas e calorias, é definida como desnutrição. 11 Quando presente nos dois primeiros anos de vida, ocasiona alterações principalmente no cerebelo, hipotálamo e hipocampo, [12][13][14] sendo a gravidade das alterações proporcional à intensidade e à duração da deficiência nutricional. 15,16 Cabe salientar que a desnutrição, apesar da tendência de redução nas últimas décadas, ainda acomete 6% dos sujeitos menores de cinco anos, dos quais a grande parcela é pertencente a famílias com baixo nível socioeconômico.…”
Section: Níveis De Evidênciaunclassified
“…The herein reviewed literature did not identify the method used in the speech test; thus, it was not possible making the comparative analysis of results reported in several studies. 15 16 17 18 Costa-Guarisco, Fernandes and Sousa (2014) investigated the audiometric configuration aspects influencing speech discrimination in downward- sloping sensorineural hearing loss cases. They analyzed values recorded for individuals subjected to SRI and SRT, but did not describe the adopted methodology (live or recorded voice).…”
Section: Discussionmentioning
confidence: 99%